Pediobius sasae (Hymenoptera: Eulophidae), a new species from galls on dwarf bamboo (Sasa nipponica) in Japan - Hansson, Christer (Zootaxa, 2006)
Pediobius sasae sp. nov. (Hymenoptera: Eulophidae) is described from Japan. This new species belongs to the “eubius-complex” of species and is compared to the species of that group. It was reared from galls induced by an unidentified gall midge of the tribe Oligotrophini (Diptera: Cecidomyiidae). The galls are formed on stems of dwarf bamboo (Sasa nipponica). Pediobius sasae is a solitary primary parasitoid on the gall midge, but possibly also acts as a secondary parasitoid of another parasitoid reared from the same host, an unidentified species of Torymus (Hymenoptera: Torymidae).